Discrepancies in recommended criteria for grading of carotid stenosis with ultrasound. (5th June 2015) - Jogestrand, Tomas; Fredén‐Lindqvist, Johan; Lindqvist, Madeleine; Lundgren, Susanne; Tillman, Ann‐Sofie; Zachrisson, Helene
Summary: The accuracy of duplex ultrasound for grading of internal carotid artery stenosis has been widely tested and shown to be high. However, different methods for measurement of the degree of carotid stenosis with the golden standard conventional angiography have been used in the different studies. This, together with other factors, has led to some confusion regarding the relation between the ultrasonographically measured flow velocity and the angiographically measured degree of stenosis. The ultrasound criteria that are used in Sweden (and in Germany) differ in an important way from the criteria recommended in North America and the United Kingdom for the same degree of angiographic stenoses. Possible reasons for the discrepancies are discussed in this article. The authors recommend absolute agreement locally whether ECST or NASCET criteria shall be used in the communication between radiologists, clinical physiologists, vascular surgeons, neurologists and other physicians involved in patient management decisions. Angle‐dependent ultrasound criteria should be used and flow velocity measurements with ultrasound should be combined with assessment of plaque burden on 2D picture.